Possibilities and Limitations of Communication of Special Purpose Civic Associations – The Case of Internal Communication of a Trade Union Active in a Company Influenced by the Groundswell Concept - Švec, Marek; Madleňák, Adam; Bezáková, Zuzana; Horecký, Jan (Communication Today, 2021)
The progressive development of marketing communication, which can also be characterised by a significant rise of the groundswell concept, has brought about the need to modify the well-established concepts and processes not only in this field of science, but also in seemingly unrelated areas, in particular collective labour relations. The traditionalist approach based on the “revolutionary trade union movement” concept favoured by special purpose civic associations (trade unions) for decades is losing its relevance. Trade unions are no longer able to attract and speak to potential trade union members – employees. The concept of “groundswell” is beginning to dominate the internal environment of employers as employees get ‘guaranteed’ information on the activities of trade unions or the very internal environment of the employer from social networks, internal software applications of the employer or its intranet (this information is questionable, if not outright misleading). Special purpose civic associations are looking for new ways to communicate with potential and current members, as they have to take into account national and European labour law, personal data protection legislation and various legal frameworks governing confidentiality duties, internal regulations governing internal communication and their own corporate identity. Based on their experience, the authors analyse the above-described trend, define possible legal and social restrictions, and outline possible solutions while respecting the nature of the special purpose civic association. The study is unique as it offers an insight into the conservative and (still) inaccessible (for nonmembers) environment of internal communication of trade unions (communication with members and potential members) based on objective interdisciplinary research combining legal science and marketing communication. The objective of the study is not to present an exhaustive overview of the issue, but to introduce new possibilities for the research in areas (where marketing plays an important role) that have so far gone unnoticed by marketing communication researchers.